1966
DOI: 10.2337/diab.15.4.258
|View full text |Cite
|
Sign up to set email alerts
|

Glomerulosclerosis in the Long-term Alloxan Diabetic Monkey

Abstract: Diabetic glomerulosclerosis has been produced in alloxan diabetic monkeys maintained from one to four years with minimal insulin dosage and high carbohydrate diet. Cataracts and dwarfism also appeared. Present limited data suggest that increased dietary fat and insulin may ameliorate these developments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0
1

Year Published

1968
1968
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 0 publications
3
7
0
1
Order By: Relevance
“…Although similar MM expansion has been identified in diabetic monkeys [Jonasson et al. 1984: Gibbs et al. 1966 and is confirmed by SEM and TEM in the current investigation, the endothe lial-mesangial layer has received relatively little attention in the monkey model.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Although similar MM expansion has been identified in diabetic monkeys [Jonasson et al. 1984: Gibbs et al. 1966 and is confirmed by SEM and TEM in the current investigation, the endothe lial-mesangial layer has received relatively little attention in the monkey model.…”
Section: Discussionmentioning
confidence: 69%
“…Several morphological studies of diabetic rhesus monkey GBMs describe BM thickening and MM expan sion similar to classical changes in end-stage human dia betic kidney disease [Gibbs et al, 1966;Jonasson et al. 1984;Jones et al.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in diabetic rats, dogs and monkeys have shown that glomerular and/or retinal capillary membrane thickening undoubtedly develops after the induction of diabetes [60][61][62][63][64][65][66][67][68][69][70][71]. This includes the streptozotocin-hyperglycaemic rats studied by Mauer [71].…”
Section: Clinical Microangiopathy and Pathologic Changes In Animals Wmentioning
confidence: 99%
“…Although the incidence of microvascular disease of patients with secondary diabetes has often not been as great as in those with idiopathic diabetes this can be attributed to the shorter survival of individuals with the primary pancreatic disease. Evidence of microvascular disease in kidney, retina or musclehas now been observed in chemically or hormonally induced diabetes of dogs, rats, and rhesus monkeys as well as in spontaneous diabetes of Chinese hamsters, KK mice and Celebes apes [59][60][61][62][63][64]. In the Celebes apes, in which the diabetes appears to be the result of infiltration of amyloid into the islets of Langerhans, the extent of muscle capillary basement membrane thickness has been correlated in an impressive manner to the degree of serum insulin decrease as well as to the serum glucose elevation [64].…”
Section: Metabolic Hypothesis Of Diabetic Microangiopathymentioning
confidence: 99%